Liga Polskich Rodzin wobec wyborów do Parlamentu Europejskiego w 2004 roku - Koziełło, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The League of Polish Families campaigned on the position that the European Union threatened the political, economic and cultural sovereignty of the Polish state. The danger was the aspiration towards closer integration of the EU which, according to the opinion of party’s leaders, was the first step towards the creation of a transnational system, and a Poland (and others among the poorer European states) dependent on the decisions of the EU’s authorities. In the new EU Poland would have to execute orders from Brussels, contrary to Polish national interests and preclusive its development. LPR took part in the election to the European Parliament, because of their desire to have their own deputies within the EU’s structures, who could stand up for better conditions of Polish membership, advantageous decisions in the EP and popularize their own political ideas in Polish and international environment. LPR took advantage of the lack of enthusiasm of Polish citizens towards Polish accession to the EU, so their anti-EU and national propaganda gained the support of a large proportion of the electorate and strengthened their position on Polish political scene.
The League of Polish Families in election to European Parliament in 2004
Keywords: League of Polish Families; Election to the European Parliament